2010
DOI: 10.1002/nau.20910
|View full text |Cite
|
Sign up to set email alerts
|

Can we predict which patient will fail drug treatment for overactive bladder? A think tank discussion

Abstract: The treatment of overactive bladder (OAB) has evolved over the past 20 years to include a number of behavioral, pharmacological, and minimally invasive treatments. After behavioral therapy, pharmacological therapy with antimuscarinics remains the mainstay of treatment. Despite this, a large number of patients will "fail" or be unsatisfied with drugs therapy. It would be extremely helpful to patients and clinicians to be able to predict who those patients are. However, there are a number of barriers. First and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 47 publications
0
29
0
2
Order By: Relevance
“…ϩ Lactobacillus crispatus (6) ϩ ϩ Lactobacillus delbrueckii (1) ϩ ϩ Lactobacillus fermentum (1) ϩ Lactobacillus gasseri (12) ϩ ϩ ϩ ϩ ϩ Lactobacillus iners (6) ϩ ϩ ϩ ϩ Lactobacillus jensenii (10) ϩ ϩ ϩ ϩ Lactobacillus johnsonii (1) ϩ Lactobacillus rhamnosus (2) ϩ ϩ Micrococcus luteus (9) ϩ ϩ ϩ ϩ Micrococcus lylae (1) ϩ ϩ Neisseria perflava (1) ϩ (Continued on following page)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ϩ Lactobacillus crispatus (6) ϩ ϩ Lactobacillus delbrueckii (1) ϩ ϩ Lactobacillus fermentum (1) ϩ Lactobacillus gasseri (12) ϩ ϩ ϩ ϩ ϩ Lactobacillus iners (6) ϩ ϩ ϩ ϩ Lactobacillus jensenii (10) ϩ ϩ ϩ ϩ Lactobacillus johnsonii (1) ϩ Lactobacillus rhamnosus (2) ϩ ϩ Micrococcus luteus (9) ϩ ϩ ϩ ϩ Micrococcus lylae (1) ϩ ϩ Neisseria perflava (1) ϩ (Continued on following page)…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of OAB is often unclear and antimuscarinic treatments aimed at relaxing the bladder are ineffective in a large percentage of OAB sufferers, thereby suggesting etiologies outside neuromuscular dysfunction (2). One possibility is that OAB symptoms are influenced by microbes that inhabit the lower urinary tract (urinary microbiota).…”
mentioning
confidence: 99%
“…For example, urgency urinary incontinence (UUI) is poorly understood chronic urinary condition that is often attributed to abnormal neuromuscular signaling and/or functioning. However, alternative or complementary mechanisms beyond neuromuscular abnormalities must be considered, since UUI pharmacological treatments aimed at the overactive bladder are ineffective in approximately half of the pharmacologically treated UUI population (7, 8). …”
Section: Introductionmentioning
confidence: 99%
“…20,21 To make matters even more complex, a specific definition of refractory OAB has not yet been established, resulting in different initiation time points with other medications or treatment modalities. 22 Canadian urologists and gynecologists generally agree that OAB treatment should be started with the lowest recommended medication dose. Our survey revealed that a slim majority of respondents (52% vs. 45%) recommend OAB pharmacotherapy for a defined time period rather than lifelong.…”
Section: Discussionmentioning
confidence: 99%